Cryptic diversity within the Megophrys major species group (Amphibia: Megophryidae) of the Asian Horned Frogs: Phylogenetic perspectives and a taxonomic revision of South Asian taxa, with descriptions of four new species - Mahony, Stephen; Kamei, Rachunliu G.; Teeling, Emma C.; Biju, S. D. (Zootaxa, 2018)
The Megophrys major species group (MMSG) is composed of typically medium to large sized frogs. Within the genus, it is the most geographically widespread clade ranging from the western Himalayas to southern Indochina. In this study, we examined in detail the extent of cryptic diversity within the MMSG-Indian populations based on molecular data (up to ten genes) using multigene concatenation and coalescent-based phylogenetic techniques, species delimitation analyses and extensive morphological data.Molecular evidence suggests a high level of hidden cryptic diversity within the MMSG, particularly within the M. major species complex (MMC), highlighting overlapping distributions, a case of potential mitochondrial transfer between two species, and tree topology discordance between phylogenetic methods and mitochondrial and nuclear data sets. Most analyses indicated distinct eastern and western clades in the MMC, and that the western clade may further divide into a northern and a southern subclade.A detailed taxonomic review of Indian members of the Megophrys major species group is provided. Previously undocumented complex nomenclatural issues involving known species are highlighted and resolved. Megophrys monticola is taxonomically redefined for the first time as a valid species since its synonymy with M. parva in 1893. The taxonomic status of two recently described species, Xenophrys katabhako and X. sanu are discussed in light of increased molecular and morphological sampling, and are synonymised with M. monticola. Megophrys monticola and M. robusta are redescribed based on their original type specimens and recently collected material. Megophrys major is neotypified and M. robusta lectotypified to remove prevailing nomenclatural instability. Four new large sized Indian MMC species are formally described from the Northeast Indian states of Arunachal Pradesh, Meghalaya and Nagaland, and Myanmar. All South Asian MMSG species are morphologically diagnosed from known congeners in the group. The geographic distributions of all taxa discussed are significantly redefined based on the revised taxonomy and extensive literature review. Morphological and molecular evidence suggests that Megophrys major sensu stricto might be endemic to Northeast India; M. glandulosa is formally removed from the Indian and Bhutan species checklists. Numerous misidentifications in literature are highlighted and corrected. In order to reduce future misidentifications of species reported from surrounding regions, high definition images of the holotypes of three Chinese species, M. glandulosa, M. medogensis and M. zhangi are provided for the first time, and a detailed description of Myanmar specimens of M. glandulosa is also given. This study provides the principle foundation for further research into the taxonomic status of the remaining, currently undescribed MMC taxa from Southeast Asia.